Complex regional pain syndrome and use of psychotropic drugs as a proxy for psychological health - Dahlin, Lars B. ; 0000-0003-1334-3099; Perez, Raquel ; 0000-0002-6273-1656; Nyman, Erika; Zimmerman, Malin ; 0000-0002-9925-3838; Merlo, Juan ; 0000-0001-8379-9708 (Scientific Reports, 2025)
We aimed to investigate the association between psychotropic drug use (proxy for psychological health) and Complex Regional Pain Syndrome (CRPS) type 1 and type 2 in upper and lower limbs. We also assessed the impact of demographic and socioeconomic factors. From a national record linkage database [4,706,821 individuals (25–64 years); CRPS type 1 = 809; type 2 = 225], prevalence ratios (PR), absolute risk (AR), and AR difference (ARD) [95% confidence intervals (CI)] were estimated by logistic and Cox regressions with constant time at risk. About 36% of CRPS individuals consumed psychotropic drugs (reference: general population 15%). Unadjusted PRs were two times higher in nerve injuries/disorders without CRPS [PR = 1.78; 95% CI: 1.73–1.82] and CRPS type 1 [2.33 (2.07–2.62)] and almost three times higher in CRPS type 2 [2.79 (2.27–3.42)]. Higher ARDs were observed in type 2, independent of level of income, and were higher for the high-income category. In type 2, ARDs were higher for middle-high/high occupational status levels. Higher ARDs were observed in nerve injuries/nerve disorders, CRPS type 1, and type 2 in immigrants, especially high for type 2. Regarding most age intervals, ARDs were higher for individuals with CRPS type 2. Individuals with CRPS, especially type 2, have high risk of impaired psychological health.